2011
DOI: 10.1371/journal.pone.0022865
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose-Mediated Oxidative Stress Impairs Cell Migration

Abstract: Deficient wound healing in diabetic patients is very frequent, but the cellular and molecular causes are poorly defined. In this study, we evaluate the hypothesis that high glucose concentrations inhibit cell migration. Using CHO.K1 cells, NIH-3T3 fibroblasts, mouse embryonic fibroblasts and primary skin fibroblasts from control and diabetic rats cultured in 5 mM D-glucose (low glucose, LG), 25 mM D-glucose (high glucose, HG) or 25 mM L-glucose medium (osmotic control - OC), we analyzed the migration speed, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 45 publications
(54 reference statements)
8
102
2
8
Order By: Relevance
“…To simulate diabetes, HG was utilized to study its effects on the fibroblasts (22). To analyze the effects of different concentrations of HG on fibroblasts, cell proliferation was monitored in different concentrations of glucose-containing media with 10% fetal bovine serum.…”
Section: Hg Induces Apoptosis and Inflammatory Responses In Fibro-mentioning
confidence: 99%
“…To simulate diabetes, HG was utilized to study its effects on the fibroblasts (22). To analyze the effects of different concentrations of HG on fibroblasts, cell proliferation was monitored in different concentrations of glucose-containing media with 10% fetal bovine serum.…”
Section: Hg Induces Apoptosis and Inflammatory Responses In Fibro-mentioning
confidence: 99%
“…34 The high glucose level was greatly associated with decreased migration, proliferation, and increased apoptosis of fibroblasts. 13,16,35,36 The blood vessels of the diabetic group had been changed in their histological appearances and expressed with thickening in their wall, constriction of the lumen, and infiltration of the wall with chronic inflammatory cells. These changes may be due to many factors, one of these factors is the action of excessive TNF alpha production, which causes clotting of the blood over the internal wall of the vessel through inactivation of the heparin like material presented in the endothelial cells that enclose the wall of the vessel, atheroma like structure laying down, and destruction of the smooth muscle fibers of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these attributes are reproduced under acute exposures to high glucose concentrations so that migration speed is reduced by ~40 % associated to a decrease in cell directionality and to non-productive protrusive events, such as loss of cell polarization, consistent with the increased activity of Rac1 and the projection of multiple lamellipodia. This experiment concluded that the generation of reactive oxygen species (ROS) may lie behind these abnormalities as they were partially or completely rescued by treatment with N-Acetyl-Cysteine (NAC) [86].…”
Section: The Diabetic Wound Fibroblastmentioning
confidence: 99%